Pengaruh Pembiayaan Mudharabah Dan Murabahah Terhadap Profitabilitas BTM Al-Kautsar Kota Makassar 2016-2022 - Andi Ulfa Ardiah Ramadhani Faisal Ulfa; Agusdiwana Suarni; Muhammad Khaedar Sahib (Universitas Merdeka Madiun, 2024)
Abstract— The purpose of this study was to determine theeffect of Mudharabah and Murabahah Financing on theProfitability of Baitut Tamwil Muhammadiyah Al-Kautsar. This study uses secondary data, which originates from thefinancial reports on mudharabah and murabahah financing published by BTM Al- Kautsar. This study uses statisticalanalysis, namely data analysis that takes into account therelationship between the dependent variable (mudharabahand murabahah) and the independent variable (profitability)with time series data in the 2016-2022 analysis period. The results of the mudharabah financing study did not have asignificant effect on profitability at BTM Al-Kautsar 2016-2022 as evidenced by the obtained t table of 2,776. Because t count is smaller t table (0.818 < 2.015). then Ho's decision is accepted and Ha is rejected. Murabahah financing has no significant effect on profitability at BTM Al-Kautsar 2016-2022 as evidenced by the obtained t table of 2,015. Becausethe t count is smaller than the table (-0.943 < 2,015). then Ho's decision is accepted and Ha is rejected.